Relation of Carotid Artery Plaque to Coronary Heart Disease and Stroke in Chinese Patients: Does Hyperglycemia Status Matter? - Zhou, Huanhuan; Wang, Xiaoyun; Zhu, Junya; Fish, Anne; Kong, Weimin; Li, Fan; Liu, Lin; Yuan, Xiaodan; Gao, Xin; Lou, Qingqing (Experimental and Clinical Endocrinology & Diabetes, 2018)
Objective To examine the association of carotid artery plaque with the incident coronary heart disease and stroke events in Chinese patients and explore whether the association differs between patients with and without hyperglycemia.Methods We evaluated plaque, and blood pressure, total cholesterol, triglycerides, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, fasting serum insulin, fasting plasma glucose, 2 h postprandial glucose and Homeostasis model assessment of insulin resistance in 253 Chinese patients. T-test and X2 test were used to compare the clinical characteristics and Binary logistic regression was applied to analyze the association of coronary heart disease and stroke between patients with and without hyperglycemia.Results Among 253 patients, 162 patients had hyperglycemia (i. e., diabetes, impaired glucose regulation and stress induced hyperglycemia) and 155 (61.3%) patients had plaque. Fasting plasma glucose, 2 h postprandial glucose and Homeostasis model assessment of insulin resistance, triglycerides, plaque were significantly higher in the hyperglycemia group than non-hyperglycemia. The incident coronary heart disease and stroke events in patients with plaque were 2.254 (95%CI,1.203–4.224) and 2.437 (95%CI,1.042–5.701) times higher than those without plaque, respectively. Among hyperglycemia subgroup, plaque was an independent risk factor for coronary heart disease (OR,3.075,95%CI,1.353–6.992) and stroke (OR,3.571,95%CI,1.460–8.737). The slopes (associations between coronary heart disease/stroke and plaque) were steeper in the hyperglycemia group than those in the non-hyperglycemia group (coronary heart disease OR,3.075 vs. 2.614; stroke OR,3.571 vs. 3.307).Conclusions The incident coronary heart disease and stroke events in patients with plaque were higher than those without plaque, and this difference was more pronounced for patients with hyperglycemia vs. those without hyperglycemia.
Keywords: carotid atherosclerotic plaque; hyperglycosemia; cardiovascular disease; apoplexy